ANALISIS PEMAHAMAN KONSEP MATEMATIS: DAMPAK HABITS OF MIND DENGAN VISUAL THINGKING - Ani Listianingsih; Suherman Suherman (Universitas Muhammadiyah Lampung, 2022)
Low understanding of mathematical concepts in mathematical learning is due to a lack of learning strategies. Therefore, this study aims to analyze the influence of Habits of Mind (HOM) on students' visual thinking in understanding mathematical concepts. Costa and Kallick's 16-category HOM questionnaires were used as research instruments. Data analysis techniques used data reduction, data presentation, and conclusion withdrawal. Based on the results of data analysis, it is known not to have the ability habits of mindfully. The results showed the profile of HOM in the understanding of the mathematics of students with visual thinking is still classified as sufficient criteria. And overall, the average Habits of Mind indicator obtained is 66.61% included in the requirements enough. Students who have Habits of Mind and good visual thinking will more easily understand mathematics. In contrast, Habits of Mind and visual thinking that is not good will be more difficult to understand mathematics.